Cervical cytokines and clearance of incident human papillomavirus infection: Hawaii HPV cohort study. Issue 5 (16th March 2013) - Scott, Mark E.; Shvetsov, Yurii B.; Thompson, Pamela J.; Hernandez, Brenda Y.; Zhu, Xuemei; Wilkens, Lynne R.; Killeen, Jeffrey; Vo, Dien D.; Moscicki, Anna‐Barbara; Goodman, Marc T.
<x xml:space="preserve">Abstract</x> Mechanisms for the control and resolution of human papillomavirus (HPV) infection of the cervix include the local production of cytokines, which control recruitment and function of cells integral to pathogen control. We established a cohort of women for long‐term follow‐up to examine the mucosal expression of antiviral (IFN‐α2), Type‐1 (IFN‐γ, IL‐12), regulatory (IL‐10), and proinflammatory (IL‐1α, IL‐1β, IL‐6, IL‐8, MIP‐1α, and TNF) cytokines in association with the clearance of incident cervical HPV infection. Interviews and specimens for HPV DNA analysis and cytokine protein measurement were obtained at baseline and at 4‐month intervals. A Cox proportional hazards model was used to study the relationship between clearance of 107 high‐risk and 111 low‐risk incident HPV infections and cytokine levels among 154 women. Positive changes from baseline levels of IL‐10, IL‐12, MIP‐1α, and TNF were associated with significantly longer times to type‐specific HPV clearance. Inverse trends in the hazard ratios associated with clearance of high‐risk HPV infections were monotonic and significant for IL‐12 (ptrend = 0.02) and TNF (ptrend = 0.02); the likelihood of high‐risk HPV clearance was reduced by 65% and 67%, respectively, among women in the highest as compared with the lowest quartile of change from baseline. Our results suggest that in women with a nontransient cervical HPV infection, proinflammatory, Type‐1, and regulatory cytokines are elevated, underscoring the long‐term commitment of local immune mediators to viral eradication.